Binary vanadium pentoxide carbon-graphene foam composites derived from dark red hibiscus sabdariffa for advanced asymmetric supercapacitor. (1st November 2021) - Ngom, B. D.; Ndiaye, N. M.; Sylla, N. F.; Mutuma, B. K.; Manyala, N.; Chaker, M.
Abstract : The development of advanced electrode materials derived from biomass for the next generation of energy storage devices, such as supercapacitors with high specific energy and specific power coupled with a good cycle stability, is required to meet the high demand for electric vehicles and portable devices. In this study, sustainable binary vanadium pentoxide carbon-graphene foam composites (V2 O5 @C-R2 HS/GF) were synthesized using a solvothermal method. The X-ray diffraction, Raman and FTIR techniques were used to study the structural properties of the composites (V2 O5 @C-R2 HS/20 mg GF and V2 O5 @C-R2 HS/40 mg GF). The SEM micrographs displayed an accordion-like morphology resulting from the graphene foam-modified V2 O5 @C-R2 HS composite. The V2 O5 @C-R2 HS, V2 O5 @C-R2 HS/20 mg GF and V2 O5 @C-R2 HS/40 mg GF composites were evaluated in a three-electrode configuration using 6 M potassium hydroxide (KOH) as an aqueous electrolyte. Furthermore, a two-electrode device was carried out by fabricating an asymmetric device (V2 O5 @C-R2 HS/GF//AC) where V2 O5 @C-R2 HS/20 mg GF was used as a positive electrode and activated carbon (AC) as a negative electrode at a cell voltage of 1.6 V in 6 M KOH. The V2 O5 @C-R2 HS/GF//AC showed a high specific energy and specific power values of 55 W h kg −1 and 707 W kg −1, respectively, at a specific current of 1 A g −1 . The asymmetric device presented a good stability test showing 99% capacity retention up to 10 000 cycles and was confirmed by the floating time up to 150 h with specific energy increasing 23.6% after the first 10 h. This article is part of the theme issue 'Bio-derived and bioinspired sustainable advanced materials for emerging technologies (part 2)'.